Technical-economic analysis on a community agricultural cooperative in the village of, in the County Vidra, Ilfov: Case study - Marius Dinică (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
In Romania, agricultural cooperatives are important pieces in the development of rural areas with permanent changes in the development of vegetable, vegetable harvesting, storage and marketing of products designed to consumption. Agricultural cooperatives contribute to improving the productivity of small farms and make possible access to product marketing, savings, credit, insurance and technology. Agricultural cooperative organization of production is determined on conditions such as: market demand, financial resources, natural environment, income, market risks. At the same time agriculture is the main source of income in rural areas.
Keywords: 330; cooperative agricultural; productivity; farm; market